2015
DOI: 10.1038/ni.3198
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA methylation dictates Cd4 expression during the development of helper and cytotoxic T cell lineages

Abstract: During development, progenitor cells with binary potential give rise to daughter cells that have distinct functions. Heritable epigenetic mechanisms then lock in gene expression programs that define lineage identity. Cd4 regulation in helper and cytotoxic T cells exemplifies this process, with enhancer- and silencer-regulated establishment of epigenetic memories for stable gene expression and repression, respectively. Using a genetic screen, we identified the DNA methylation machinery as essential for maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 42 publications
(49 reference statements)
8
90
0
Order By: Relevance
“…Epigenetic gene silencing largely relies on two processes: methylation of DNA itself (at position 5 of cytosine [5 mC] typically within palindromic CpG dinucleotide pairs) (62, 63) and post-transcriptional modifications of histones, the core proteins permitting assemblage of eukaryotic chromatin into nucleosomes (64). While there is currently no reported evidence that histone modifications contribute to Cd4 silencing, DNA methylation has recently been shown to be a key player (65). CpG methylation, initiated by DNA methyl transferases Dnmt3a and Dnmt3b, and transmitted during cell division by Dnmt1, is thought to promote gene silencing either by direct inhibition of transcription factor binding or by recruiting methyl CpG-binding proteins associated with transcription repression complexes (66).…”
Section: Control Of Cd4 Expression In Mature T Cells: An Epigenetic Epicmentioning
confidence: 99%
See 2 more Smart Citations
“…Epigenetic gene silencing largely relies on two processes: methylation of DNA itself (at position 5 of cytosine [5 mC] typically within palindromic CpG dinucleotide pairs) (62, 63) and post-transcriptional modifications of histones, the core proteins permitting assemblage of eukaryotic chromatin into nucleosomes (64). While there is currently no reported evidence that histone modifications contribute to Cd4 silencing, DNA methylation has recently been shown to be a key player (65). CpG methylation, initiated by DNA methyl transferases Dnmt3a and Dnmt3b, and transmitted during cell division by Dnmt1, is thought to promote gene silencing either by direct inhibition of transcription factor binding or by recruiting methyl CpG-binding proteins associated with transcription repression complexes (66).…”
Section: Control Of Cd4 Expression In Mature T Cells: An Epigenetic Epicmentioning
confidence: 99%
“…Importantly, the symmetry of CpG motifs allows their methylation to be ‘copied’ by Dnmt1 to newly synthesized strands during DNA replication, thereby ensuring truly epigenetic inheritance of this mark. Indeed, the Cd4 locus is hypermethylated in CD8 + T cells and hypomethylated in CD4 + T cells (65). Hypermethylation of the Cd4 locus is established early at the DN3 stage and maintained through the DP stage to CD8 SP, in a silencer-dependent manner.…”
Section: Control Of Cd4 Expression In Mature T Cells: An Epigenetic Epicmentioning
confidence: 99%
See 1 more Smart Citation
“…Precise temporal control of methylation and demethylation is essential for the development and differentiation of both T cells [64] and intestinal epithelial crypt cells [65], indicating that MBD2 may contribute to the interpretation of DNA methylation in these tissues. For example, MBD2 has a role in T-cell development that is partially dependent on the methylation status of critical genes such as Foxp3 [50,66], but also has a role in the innate immune system to indirectly affect T-cell activation and differentiation [49].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that a stable DNA-methylation program at the proximal enhancer of the cd4 locus (CD4) is essential to enforce cd4 gene silencing in CD8 + T cells, whereas CD4 + T cells lack this program, suggesting an important role of epigenetic programming in securing cell-identity during T-cell development [49]. Genome-wide DNA-methylation profiling of naïve and effector virus-specific CD8 + T cells during acute LCMV infection have revealed that many promoters and putative regulatory cis-elements of effector genes become demethylated during effector T-cell differentiation, along with differential methylation programming at naïve/effector-specific transcription factor binding sites [47].…”
Section: Challenges Of Immune Checkpoint Blockade Therapymentioning
confidence: 99%